Maintenance of statin use over 3 years following acute coronary syndromes: a national data linkage study (ANZACS-QI-2). Issue 10 (16th January 2014) - Grey, Corina; Jackson, Rod; Wells, Sue; Thornley, Simon; Marshall, Roger; Crengle, Sue; Harrison, Jeff; Riddell, Tania; Kerr, Andrew
Abstract : Objective: To describe patterns of statin use and predictors of poor maintenance over a 3-year period following an acute coronary syndrome (ACS). Methods: National hospitalisation, mortality and pharmaceutical dispensing data were linked for all subjects aged 35–84 years discharged from a public hospital with an ACS in New Zealand in 2007. A Medication Possession Ratio (MPR; percentage of follow-up days patients were dispensed statins) was calculated for each patient. Adequate maintenance was defined by a MPR ≥80%. Results: In 2007, 11 348 patients aged 35–84 years were discharged from hospital with ACS. Within 90 days of discharge, 83% had received a statin. Over the follow-up period, 66% were adequately maintained on a statin (MPR ≥80%): 69% in the first year, 67% in the second year and 66% in the third year. Patients taking statins prior to admission and those who underwent a coronary procedure were 20–50% more likely to have a MPR ≥80% over 3 years than others. In contrast, people aged 35–45 years and those of Maori or Pacific ethnicity were 13–25% less likely to have a MPR ≥80% than those aged 55–64 years and Europeans. Conclusions: One-third of patients were not adequately maintained on statins over the 3-year period following ACS, but 82% of those on a statin prior to admission had an MPR ≥80% over 3 years of follow-up. These findings define achievable treatment levels and identify groups who may benefit from efforts to improve statin use.